Morphophysiological features of seeds and seedlings between wild and cultivated genotypes of Hevea brasiliensis - de Carvalho, J.C; Miranda, M J D S; Kramer, Y.V; Reis, A R S; Goncalves, J F D C (Journal of Tropical Forest science, 34(4): 383-392., 2022)
Morphophysiological changes related to germination and initial seedling growth of different Hevea brasiliensis genotypes (wild and cultivated) were investigated. The seeds were sterilised before their biometric analyses were performed and the imbibition curve was mapped. Parallel to these assays, the morphology of the germination/post-germination stages and seed health testing were monitored from seeds germinated in washed sand and on filter paper respectively. The wild and cultivated (PB260) genotypes showed different behaviour patterns during the events of germination and post-germination. The seeds and seedlings could be differentiated by morphological characteristics associated with the size and colour of the seeds, as well as by the rapid imbibition of water, germination, and initial growth. Germination was characterised as being of a hypogeal, cryptocotyledonous type, with root protrusion between 6 and 8 days, and complete seedling formation at 23 and 25 days for wild and cultivated seeds respectively. The morphophysiological variables in seeds and seedlings of H. brasiliensis are useful in breeding programmes where seed selection and seedling performance evaluation focus on wild genotypes, which can add functional characteristics in favour of clones currently used in rubber tree plantations.
Keywords: Morphophysiological markers; Seed selection; Seedlings performance; Rubber tree breeding